Screw dislocation in a Rashba spin-orbit coupled $$α$$ α - $$T_3$$ T 3 Aharonov–Bohm quantum ring - Mijanur Islam; Saurabh Basu (Scientific Reports, 2024)
Abstract In this paper we investigate the effect of a topological defect, such as a screw dislocation in an $$α$$ α - $$T_3$$ T 3 Aharonov–Bohm quantum ring and scrutinized the effects of an external transverse magnetic field and Rashba spin-orbit coupling therein. The screw dislocation yields an effective flux which reshape the periodic oscillations in the persistent current in both charge and spin sectors, with a period equal to one flux quantum. Moreover, they suffer a phase shift proportional to the degree of dislocation, and include scattering effects due to the dislocation present in the system. Such tunable oscillation of the spin persistent current highlights applications of our system as potential spintronic devices. Further, the behaviour of the current induced by the Burgers vector ( $$b^z$$ b z ) which denotes the strength of the dislocation is investigated in the absence and presence of an external magnetic field. In both the scenarios, an almost linear decrease in the current profile as a function of the Burgers vector is observed. Notably, without the external magnetic field, the Burgers current suffers a back flow for $$α =1$$ α = 1 (dice lattice), while in the presence of the external magnetic field, for other values of $$α$$ α (e.g., $$α =0.5$$ α = 0.5 ) this back flow occurs for a specific value of $$b^z$$ b z . Additionally, the presence of the distortion induces a chirality effect, giving rise to an additional chiral current even in the absence of an external field. Furthermore, in the absence of field, the Burgers spin current initially rises, attains a maximum before diminishing as $$b^z$$ b z is enhance for all values of $$α$$ α . However, such a non-monotonicity in the Burgers spin current is conspicuously non-existent in the presence of an external field. The chiral current discussed above may hold important applications to spintronics.